Pendapatan Usaha Mahalona Kopi - Malika Hayatun Nisa; Yuli Manda Sari; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Journal of Management and Creative Business, 2023)
The purpose of this visit was to find out how the income in the Mahalona Coffee business. Income is very important in the sustainability of a business, because income is the object of business activities. The more products produced by Mahalona Kopi, the higher the probability of net income received by entrepreneurs. Vice versa, the fewer products produced by Mahalona Kopi, the lower the net income obtained. The data presented in this article is carried out within one day, namely in April 2023 at the Mahalona Coffee trading business location at ruko city walk galuh mas raya XI A number 2-23. Using primary data obtained by conducting direct interviews with business owners, namely Abiyyu Nur Faris. In the data collected, Mahalona Coffee has a fairly large monthly income, with 9 workers. Therefore, this interview aims to find out the income in the Mahalona Coffee business. The methods used are observation, direct interviews, and documentation, such as taking photos or videos when collecting information related to Mahalona Kopi.